Mapping, Society, and Technology - Manson, Steven (Open textbook library., 2017)
This book is about how to read, use, and create maps. Our exploration of maps will be informed by a contextual understanding of how maps reflect the relationship between society and technology, and how mapping is an essential form of scientific and artistic inquiry. We will also explore how mapping is used to address a variety of societal issues, such as land use planning and political gerrymandering. You will gain insight into the technical underpinnings of mapping as a science approach, complement on-going interest and activities, or provide an applied focus for research or policy.